Golf legends - Italia, Bob, 1955- (Bloomington, Minn. : Abdo & Daughters, 1990)
Describes the lives of sports legends Lee Trevino, Arnold Palmer, Jack Nicklaus, Sam Snead, Bobby Jones
Keywords: Golf -- History; Golfers -- Biography